Symbols and professional ceremonies of nursing - relict of the past or the professional value? - Zarzycka, Danuta; Dobrowolska, Beata; Ślusarska, Barbara (Nursing Problems / Problemy Pielęgniarstwa, 2009)
Introduction. Contemporary symbolism of social life has experienced a crisis with relation to the mental/awareness-related promotion or celebrations. Therefore it is worthreflecting on the characteristics of professional symbols and ceremonies in nursing in order to establish an opinion with regard to the future of this dimension of nursing image creation. Aim. The objective of the research is to show the meaning of professional symbols and ceremonies in the contemporary nursing. Material and methods. The analysis of literature basing on the following criteria: - the meaning of professional symbols and ceremonies in communicating in selected relationships, e.g. a nurse-society; - the meaning of professional symbols and ceremonies in the education process; - the meaning of professional symbols and ceremonies in creation of Polish nursing image. Results and conclusions: 1. The meaning of symbols and ceremonies in communication may be generally defined as: normative, expressive and instrumental. 2. Professional symbolism and its promotion is an irreplaceable education method. 3. The system of symbols functioning in nursing can be defines as the culture of nursing. The value of symbolism in creation of complex professional identity of nursing indicates the possibility of taking up of activities towards its “animation”.